Cambridge english pronouncing dictionary CD-ROM - Jones, Daniel (Cambridge University Press, 2006)
A network CD-ROM version of the classic English Pronouncing Dictionary, in a fully updated edition, with a fully updated word list including people and places recently in the news. British and American pronunciations are shown for every word, using the International Phonetic Alphabet, and edited by eminent phoneticians in the UK and the US. This is the only pronunciation dictionary available in a CD-ROM format, which contains recordings of every headword, advanced searching facilities, the ability to record and evaluate the user's own pronunciation, and a wealth of interactive pronuciation exercises.